2023
DOI: 10.1186/s13098-023-01052-7
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet lowers all-cause and cardiovascular mortality for patients with metabolic syndrome

Abstract: A Mediterranean-style diet (MED) can promote people lengthen the span of life and avoid atherosclerotic cardiovascular disease (ASCVD) in primary prevention. Metabolic syndrome (MetS) can significantly reduce life expectancy and increase the risk of ASCVD. However, few studies have focused on the role of the Mediterranean diet in patients with MetS. Participants in the National Health and Nutrition Examination Survey (NHANES) with MetS (N = 8301) from 2007 to 2018 were examined. A 9-point evaluation scorewas u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Additionally, the available studies also demonstrated a close link between early-onset AGA and MetS, CVD, IR, and dyslipidemia. Interestingly, these chronic diseases are also strongly related to the risk factors for early-onset AGA, such as smoking [77,78] and dietary habits [79][80][81]. Therefore, this emphasizes the importance of lifestyle modifications in individuals with early-onset AGA to prevent these co-existing health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the available studies also demonstrated a close link between early-onset AGA and MetS, CVD, IR, and dyslipidemia. Interestingly, these chronic diseases are also strongly related to the risk factors for early-onset AGA, such as smoking [77,78] and dietary habits [79][80][81]. Therefore, this emphasizes the importance of lifestyle modifications in individuals with early-onset AGA to prevent these co-existing health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1999, the survey has been carried out, with updated data sets made accessible every two years at https://www.cdc.gov/nchs/nhanes/index.htm [ 25 ]. All survey participants supplied informed written agreement, which was approved ethically by the Ethics Review Board of the NCHS [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The International Classification of Diseases, Tenth Revision (ICD-10) codes were used to identify causes of death to obtain data on mortality follow-up from NHANES Public-use Linked Mortality Files ( https://www.cdc.gov/nchs/data-linkage/mortality.htm ). ICD-10 codes are alphanumeric codes that are used to track diseases and other health-related problems [ 19 ]. By using these codes, researchers can track and categorize deaths based on the leading causes of death CVD deaths were categorized using certain ICD codes (054–068).…”
Section: Methodsmentioning
confidence: 99%